Unintended Effects From the Expansion of the Non-Contributory Health System in Peru - Torres, Jose (IMF Working Papers; Working Paper ;, 2021)
Over the last two decades, the Peruvian government has made great efforts to improve access to health care by significantly augmenting the coverage of the non-contributory public health care system Seguro Integral de Salud (SIS). This expansion has a positive impact on welfare and public health indicators, as it limits the risk of catastrophic health-related costs for previously uninsured individuals and allows for the appropriate treatment of illnesses. However, it also entails some unintended consequences for informality, tax revenues, and GDP, since a few formal agents are paying for a service that the majority of (informal) agents receive for free. In this paper, we use a general equilibrium model calibrated for Peru to simulate the expansion of SIS to quantify the unintended effects. We find that overall welfare increases, but informality rises by 2.7 percent, while tax revenues and output decrease by roughly 0.1 percent. Given the extent of the expansion in eligibility, the economic relevance of these results seems negligible. However, this occurs because the expansion of coverage was mostly funded by reducing the spending per-insured person. In fact, we find larger costs if public spending is increased to improve the quality of service given universal coverage.